PEWARNAAN PADA GRAF BINTANG SIERPINSKI - Siti Khabibah (Universitas Jenderal Soedirman, 2017)
This paper discuss about Sierpinski star graph , which its construction based on the Sierpinski triangle. Vertex set of Sierpinski star graph is a set of all triangles in Sierpinski triangle; and the edge set of Sierpinski star graph is a set of all sides that are joint edges of two triangles on Sierpinski triangle. From the vertex and edge coloring of Sierpinski star graph, it is found that the chromatic number on vertex coloring of graph is 1 for n = 1 and 2 for ; while the chromatic number on edge coloring of graf is 0 for n = 1 and for